Board size and firm value in the context of Malaysia: a conceptual framework - Asmira Syakirraa; Chia, Yee Ee (Penerbit UMS, 2023)
This paper presents a conceptual framework between board size and firm value in the context of Malaysia. A comprehensive study of the impact of corporate governance on firm value was conducted. Theoretically, agency theory and resource dependence theory are two frameworks that can be used to analyse the relationship between board size and firm value. Agency theory states that smaller boards of directors are associated with better firm performance and higher firm value because they lead to better decision-making and more effective oversight. Resource dependence theory, on the other hand, suggests that larger boards are able to access external resources, a diverse group of backgrounds, skills, and expertise in specific areas relevant to the company’s operations will increase the value of the firm. Considering the countervailing positive and negative effects of board size on firm value, this paper predicts a non-monotonic relationship between board size and the firm value of listed companies in Malaysia. Therefore, it is important for policymakers to consider the composition and size of the board of directors to ensure effective corporate governance and contribute to the overall success of the company.